Etika Bermedia Sosial Dalam Perspektif Al-Qur'an: Analisis Tafsir Qs. Al-Hujurat Ayat 6, 11 Dan 12 - Selpi Indramaya; Faiz Tsabitul Aqdam; Muhammad muhydiin; Radhi Pratama; Lailatul Mardiah; Miftahul Rizky; Fitra Khairul Dzakwan (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The development of social media has brought significant changes to the communication patterns of modern society, but it has also generated various ethical issues, such as the spread of unverified information, hate speech, insults, prejudice, and the disclosure of personal matters in digital spaces. This study aims to analyze the concept of social media ethics from the perspective of the Qur’an through a tafsir study of QS. Al-Hujurat verses 6, 11, and 12. This research employs a qualitative approach using a library research method and a thematic interpretation (tafsir maudhu’i) approach. The research data were obtained from primary sources, including the Qur’an and classical as well as contemporary tafsir works, and secondary sources consisting of scholarly articles and relevant literature on Islamic communication ethics and digital literacy. Data analysis was conducted using content analysis techniques by identifying the ethical values contained in these verses and relating them to contemporary digital communication phenomena. The findings reveal that QS. Al-Hujurat verses 6, 11, and 12 establish a paradigm of social media ethics based on three main principles: information verification through the concept of tabayyun, respect for human dignity through the prohibition of insulting and degrading others, and social responsibility through controlling prejudice, tajassus, and ghibah. This study demonstrates that social media ethics from the Qur’anic perspective is not merely normative but can be developed as an Islamic digital literacy framework that integrates technological competence with moral and spiritual values. This study contributes to contemporary Qur’anic studies by offering a model of digital communication ethics based on Qur’anic principles that is relevant to the challenges of today’s information society.